ANALISIS SITUASI PERMASALAHAN SAMPAH DI DESA WANGUK KABUPATEN INDRAMAYU DAN KEBIJAKAN PENANGGULANGANNYA - Tita Noviana Tiarni Junaedi; Linda Nurhilma; Muhammad Arief Baiquni (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2026)
Almost all activities carried out by humans do not escape from traces or residual activities or in other words, waste. Without realizing it, humans are producers of waste and if processing is not paid attention to, waste will cause many problems. This research aims to analyze the waste problem situation in Wanguk Village, as well as evaluate the management policies that have been implemented. The research method used is qualitative research with a descriptive observational design. Research techniques were carried out by means of field surveys, focus group discussions involving participants, interviews and literature studies. The participants used in this research were representatives of village officials. The results of the research state that waste management in the village is still not good, this is due to a lack of public awareness, lack of waste management facilities, existing management policies include education programs and development of waste management infrastructure. and geographical location.